A nationwide population‐based survey on the prevalence and risk factors of symptomatic pelvic organ prolapse in adult women in China – a pelvic organ prolapse quantification system‐based study. (25th March 2021) - Pang, H; Zhang, L; Han, S; Li, Z; Gong, J; Liu, Q; Liu, X; Wang, J; Xia, Z; Lang, J; Xu, T; Zhu, L
Abstract : Objective: To determine the prevalence, risk factors and burden of symptomatic pelvic organ prolapse (POP) in adult Chinese women. Design: A nationwide cross‐sectional study. Setting: Six geographic regions of mainland China. Participants: Women aged ≥20 years old were included using a multistage, stratified, cluster sampling method from February 2014 through March 2016. Methods: We conducted a nationwide epidemiological survey. 'Symptomatic POP' was determined by a screening questionnaire and physical examination. Main outcome measurements: Prevalence, odds ratio (OR). Results: A total of 55 477 women (response rate, 92.5%; mean age, 45.1 years old) were included. The prevalence of symptomatic POP was 9.6% (95% CI 9.3–9.8%) and it increased with age in each stage ( P < 0.05). Symptomatic POP‐Q stage II, which mainly involved anterior compartment prolapse, was the most common (7.52%). Minor/moderate burden of symptomatic POP was the most common, with a prevalence of 9.7% (95% CI 9.5–10.0%). The odds for each type of symptomatic POP increased with age (>50 vs 20‐29 years old in symptomatic POP‐Q stage II or higher, OR increased from 1.34 [95% CI 1.32–1.45] to 7.34 [95% CI 4.34–12.41]) and multiple vaginal deliveries (multiparous [≥3] vs nulliparous in symptomatic POP‐Q stage II or higher, OR increased from 1.91 [1.71–2.13] to 2.78 [2.13–3.64]). Conclusions: We found a lower prevalence of symptomatic POP than that found in other surveys. The main type of symptomatic POP was anterior compartment prolapse, indicating that it should be considered first. Older age and multiple vaginal deliveries increased the odds of each type of symptomatic POP. Tweetable abstract: The prevalence of female symptomatic pelvic organ prolapse (POP) was 9.6% in China. It is related to old age and multiple vaginal deliveries. Tweetable abstract: The prevalence of female symptomatic pelvic organ prolapse (POP) was 9.6% in China. It is related to old age and multiple vaginal deliveries.